GLOBAL MEDIA AND NARRATIVE FRAMING IN INTERNATIONAL RELATIONS - Nigina Ikromova (Bright Mind Publishing, 2025)
Global media has developed into one of the main spheres of worldwide influence in the twenty-first century. The structuring of narratives through news media and internet platforms becomes a strategic tool for influencing global opinion as soft power in diplomacy becomes more important. Using important case studies and theoretical ideas, this study investigates how story framing functions as an influencing mechanism in international relations. It urges critical media literacy among international actors and makes the case that controlling narratives is just as important in contemporary diplomacy as having economic or military might.
Keywords: Narrative framing, soft power, international relations, global media, public diplomacy, disinformation, digital diplomacy.